Co-production of digital public services in Austrian public administrations - Noella Edelmann; Ines Mergel (Administrative Sciences, 2021)
In the digital transformation of public administrations, objectives are no longer simply the implementation of new technology, but the involvement of all stakeholders into the process of digitalization. The Digital Roadmap of the Austrian government emphasizes the need of co-production of public services as a key element to public service delivery and, subsequently, innovation of the public sector. To understand how co-production in digital service delivery is implemented in Austria, we conducted interviews with 41 experts from public administrations in order to understand who is involved in such processes, how they are involved, and what outcomes are to be achieved.
Keywords: 350; digital transformation; public administration; citizen participation; co-production; public value outcomes